Evaluation of Inaccuracy Analysis of Returning Inpatient Medical Record Documents at “X” Hospital in Malang City - Ratna Wardani; Fita Rusdian Ikawati (Journal for Quality in Public Health, 2022)
This study uses a qualitative method, the data collection is in the form of interview and observation techniques on medical record Assembling officers, registration officers, verification officers, distribution officers and nurses at RS "X" Malang City. Thus, the qualitative method in this study was used to find out what factors caused the inaccuracy in the time of providing and distributing medical record files to the assembling section in terms of input, process and output factors. The results showed that the causes of the delay in returning Medical Record Documents (DRM) included patients who registered in 2 polyclinics until no medical records were found, and a missfile where the medical record file was still in inpatient because the data had not been filled out completely by the doctor in charge of the patient and had not been completed and returned to the medical record installation section, so this will slow down in finding the medical record file.